2015
DOI: 10.1007/978-3-319-27683-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Justification Logic

Abstract: We present a probabilistic justification logic, PPJ, as a framework for uncertain reasoning about rational belief, degrees of belief and justifications. We establish soundness and strong completeness for PPJ with respect to the class of so-called measurable Kripke-like models and show that the satisfiability problem is decidable. We discuss how PPJ provides insight into the well-known lottery paradox.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…As a continuation of [15] and [16] we showed that results for justification logic and probabilistic logic can be nicely combined. Recall that the probabilistic justification logic PJ is obtained by adding probability operators to the justification logic J.…”
Section: Final Remarks and Conclusionmentioning
confidence: 70%
See 2 more Smart Citations
“…As a continuation of [15] and [16] we showed that results for justification logic and probabilistic logic can be nicely combined. Recall that the probabilistic justification logic PJ is obtained by adding probability operators to the justification logic J.…”
Section: Final Remarks and Conclusionmentioning
confidence: 70%
“…Observe that by Theorem 9 and our previous remarks we have that, for a decidable schematic and axiomatically apropriate constant specification, the derivability problem for the logic PJ CS is Π p 2 -complete. In [16] the probabilistic justification logic PPJ is defined. PPJ is a natural extension of PJ that supports iterations of the probability operator as well as justifications over probabilities.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…the logic of justification graphs axiomatised in Section 3. Our logic and its axiomatisation incorporates a partial order on the set of beliefs that underlies their prioritization during conflict resolution, which contrasts with the probabilistic extension of justification logic outlined in [22].…”
Section: Related Workmentioning
confidence: 99%
“…because this coin looks similar to a counterfeit coin I have seen some time ago". As another application of PPJ, in [19] we have shown that the lottery paradox [23] can be analysed in this logic. The lottery paradox goes as follows: assume that we have 1, 000 tickets in a lottery where every ticket has the same probability to win and there is exactly one winning ticket.…”
Section: Background and Related Workmentioning
confidence: 99%